Incidence of Dating Violence in Middle Adolescence - N. Reski Septi Dewi; Ariani Fatmawati; Bhekti Imansari (MEDIA ILMU KESEHATAN, 2023)
Background: Middle adolescents interact more with the opposite sex so that mutual liking arises, interest in the opposite sex will continue to undergo a relationship called dating. Middle age is emotionally and mentally unstable so that if there are problems in dating it will cause or will experience dating violence.Objective: The aim of this study was to determine the incidence of dating violence in middle adolescents.Methods: This research is descriptive quantitative. The population in this study were middle adolescents in Ciparay District School, Bandung Regency, with a total sample of 295 respondents.Results: The results showed that the description of the incidence of physical violence was small (5.8%), threatening behavior was small (11.2%), sexual violence was almost half (37.6%), verbal emotional violence was almost half (30.2%), relational violence was small (18.0%), and in cyber violence most of 51.2%.Conclusion: The conclusion is that almost all adolescents are dating violence. Schools form a task force for the Prevention and Handling of Sexual Violence.